The association of increased SNAP benefits during COVID-19 with food insufficiency and anxiety among US adults: a quasi-experimental study - Kaitlyn E Jackson; Amy Yunyu Chiang; Rita Hamad (Cambridge University Press, 2024)
Abstract Objectives: The COVID-19 pandemic and subsequent policy response to mitigate disease spread had far-reaching impacts on health and social well-being. In response, the Supplemental Nutrition Assistance Program (SNAP) underwent several pandemic-era modifications, including a 15 % monthly benefit increase on January 1, 2021. Research documenting the health effects of these SNAP modifications among low-income households and minoritized groups who were most impacted by the economic fallout during the first years of the pandemic is lacking. We aimed to estimate the health effects of the 15 % SNAP benefit increase in January 2021, among SNAP-eligible US households. Design: We estimated the effects of the SNAP increase on food insufficiency, mental health, and financial well-being using a rigorous quasi-experimental difference-in-differences (DID) analysis. Setting: August 19, 2020, to March 29, 2021. Participants: Participants were drawn from the national US Census Bureau Household Pulse Survey waves 13-27 (n 44 477). Results: Compared with SNAP-eligible non-recipients, SNAP-eligible recipients experienced decreased food insufficiency (-1·9 percentage points (pp); 95 % CI -3·7, -0·1) and anxiety symptoms (-0·09; 95 % CI -0·17, -0·01), and less difficulty paying for other household expenses (-3·2 pp; 95 % CI -4·9, -1·5) after the SNAP benefit increase. Results were robust to alternative specifications. Conclusions: Expansions of federal nutrition programmes have the potential to improve health and financial well-being. This study provides timely evidence to inform comprehensive safety net nutrition policies during future economic crises and public health preparedness response plans.